Education In The Emirate Of Bukhara (Based On The Life and Work Of The Rulers) - Akhmadov Olimjon Shodmonovich (Buletin Antropologi Indonesia, 2025)
This article reveals the personal human qualities of Muhammad Rahimkhan, Amir Shohmurod, Amir Haydar and Amir Alimkhan, the emirs of Bukhara from House of Manghit, as well as their contribution to the field of education. As well article examines the development of pedagogical ideas introduced by the new enlighteners in Bukhara from the late 19th century and the 30s of the 20th century and to develop scientific and practical recommendations for incorporating their progressive views into the modern educational process. Moreover, clarified that in the late 19th and early 20th centuries, the main focus in the Bukhara Emirate was on religious education, while the teaching of secular knowledge remained secondary, and that the Jadids, recognizing their lag behind the world in terms of science and education, saw this as one of the most significant reasons to initiate a radical reform of the education system.